The Influence of Competency on Employee Performance in Village Governance in Bulungan Regency: The Role of Organizational Support and Work Environment Moderation - Ester Julan Lian; Erick Karunia; Shalahuddin Shalahuddin; Mappa Panglima Banding; Muh. Irfandy Azis (Jurnal Economic Resource, 2026)
This study examines the effect of competence on employee performance in village governance in Kabupaten Bulungan, with organizational support and work environment as moderating variables. The research aims to analyze direct and moderating relationships among these variables. A quantitative approach was applied to survey data from 196 Village Consultative Body members, and the data were analyzed using SmartPLS with SEM-PLS. The results show that competence, organizational support, and work environment positively affect performance. Organizational support significantly moderates the relationship negatively, while work environment moderation is not significant. The findings imply that improving village governance performance requires strengthening both individual competence and institutional support systems.